(3EOGQI efXeGJ GdCYeGd GdNGUI (B/s - (3GdYLQhOj, OjajOs ((3GdbGgQI(B: s (3GdecJH GdYQHj ddeYGQa(B, s, 2011)
(3eaghe GdGOGQI h JWhQgG GdJQjNj , eaghe GdYedjI GdGOGQjI h NUGFUgG GdYedjI , GdJNWjW (B: (3eaghg h COhGfg h eaghe GdJfXje , Gdgjcd GdJfXjej h GdNQGFW GdJfXjejI h GSJNOGe GdfeGPL GdcejI aj eLGd GdJfXje , JYQa GdJhLjg h CQcGfg , GdQbGHI h CfhGYgG , GdJOab GdeYfhj , GdeSDhdjI GdGLJeGYjI h fTCJgG h GdeSDhdjI GdCNdGbjI ddeOjQjf(B.s
Keywords: (3EOGQI GdGYeGds; (3GdEOGQIs; (3GdJNWjWs; (3efXeGJs